Effects of 1α,25-Dihydroxyvitamin D3 on the Pharmacokinetics of Procainamide and Its Metabolite N-Acetylprocainamide, Organic Cation Transporter Substrates, in Rats with PBPK Modeling Approach - Anusha Balla; Yoo-Seong Jeong; Hyo-Jung Kim; Yun-Jong Lee; Suk-Jae Chung; Yoon-Jee Chae; Han-Joo Maeng (MDPI AG, 2021)
In this study, possible changes in the expression of rat organic cationic transporters (rOCTs) and rat multidrug and toxin extrusion proteins (rMATEs) following treatment with 1α,25-dihydroxyvitamin D3 (1,25(OH)2D3) were investigated. Rats received intraperitoneal administrations of 1,25(OH)2D3 for four consecutive days, and the tissues of interest were collected. The mRNA expression of rOCT1 in the kidneys was significantly increased in 1,25(OH)2D3-treated rats compared with the control rats, while the mRNA expressions of rOCT2 and rMATE1 in the kidneys, rOCT1 and N-acetyltransferase-II (NAT-II) in the liver, and rOCT3 in the heart were significantly decreased. Changes in the protein expression of hepatic rOCT1 and renal rOCT2 and rMATE1 were confirmed by western blot analysis. We further evaluated the pharmacokinetics of procainamide (PA) hydrochloride and its major metabolite N-acetyl procainamide (NAPA) in the presence of 1,25(OH)2D3. When PA hydrochloride was administered intravenously at a dose 10 mg/kg to 1,25(OH)2D3-treated rats, a significant decrease in renal and/or non-renal clearance of PA and NAPA was observed. A physiological model for the pharmacokinetics of PA and NAPA in rats was useful for linking changes in the transcriptional and translational expressions of rOCTs and rMATE1 transporters to the altered pharmacokinetics of the drugs.